OPTIMASI FORMULA KUAH JAHE DALAM PENGEMBANGAN WEDANG TAHU SEBAGAI PANGAN FUNGSIONAL - Nurheni Sri Palupi; Larasati Ines Wardiani; Budi Nurtama (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2016)
Soft tofu dessert is a traditional food made from soft tofu and ginger drink. The traditional ginger drinkcontains antioxidant compounds. There are many varieties of ginger in Indonesia which have different antioxidant activities. Partially subtitution of Zingiber officinale var. Rubrum by Zingiber officinale var. Amarum was expected to improve sensory characteristics and antioxidant activity of traditional ginger drink. The objective of this research was to improve the formula of ginger drink based on sensory characteristics and antioxidant activity in the development of soft tofu dessert as a functional food. Optimization was done by Response Surface Methodology (RSM) based on the value of lightness (L) and °Hue of ginger drink which measured by Chromameter and antioxidant activity determined by DPPH method. Independent variables using in this optimization were the concentration of ginger and brown sugar. The optimal formula of ginger drink and its application in soft tofu dessert were analyzed by the hedonic rating method. The result of optimal formula consisted of 10.00% Zingiber officinale var. Rubrum, 9.99% Zingiber officinale var. Amarum, and 10.00% brown sugar with a desirability value of 0.822. The antioxidant activity of the optimal formula of ginger drink was AEAC 553.40 ppm, lightness (L) value was 40.03, and oHue was 74.67. The result of sensory test showed that the panelist preference for optimal formula was higher than for the traditional formula of ginger drink, while the acceptance level of the optimal formula was also higher than the tradisional formula of soft tofu dessert.